The fictitious domain method and homotopy as a new alternative for multidimensional partial differential equations in domains of arbitrary shape - Gavrilyuk, I.P.; Makarov, V.L. (Reports of the National Academy of Sciences of Ukraine, 2019)
The ideas of the method of fictitious domains and of homotopy are united with the aim to reduce the solution of multidimensional partial differential equations in an arbitrary domain to an exponentially convergent sequence of problems in a parallelepiped (rectangle in the 2D case). This makes it possible to reduce the amount of computational work due to the absence of the need for the triangulation of a domain.